POTENSI PENGEMBANGAN WISATA HALAL DALAM MENINGKATKAN EKONOMI MASYARAKAT (Studi Objek: Wisata Halal Kebun Kurma Desa Karanglo Sukorejo Pasuruan) - Sukamto, Sukamto; Farida, Alimatul; Fahmul Iltiham, Muhammad; Solichah, Mar'atus (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
The tourism industry plays an important role in the global economy as it is considered as one of the contributing factors to employment growth and economic growth in any country. In Karanglo Sukorejo Village, Pasuruan, there are tours where the majority of the people are Muslim, so there is a need for an understanding of tourism in accordance with sharia rules and principles. Therefore, researchers conducted research with the title